The Effect of Current Ratio, Net Profit Margin and Total Asset Turnover on Capital Structure in Basic and Chemical Industry Sector Companies in 2018-2020 - Sherina; Susanti; David (LPPM STIE EKA PRASETYA, 2022)
For companies, increasing the value of the company is considered very important to strengthen its financial stability, because changes in the capital structure can cause changes in the value of the company. A good capital structure is one whose value is less than one. If the value of the capital structure is more than one, the company is considered to have a greater amount of debt than the amount of its own capital. This study aims to examine the effect of the current ratio, net profit margin, and total asset turnover on the capital structure. This study uses a quantitative approach with a sample population of 74 companies. By using purposive sampling, the sample that meets the criteria is 31 companies. The results show that the current ratio partially affects the capital structure. Partially, net profit margin and total asset turnover have no effect on capital structure. Simultaneously the current ratio, net profit margin and total asset turnover affect the capital structure of the basic and chemical industries listed on the Indonesia Stock Exchange for the 2018-2020 period.